A rare case of parathyroid crisis with respiratory failure successfully treated using extracorporeal membrane oxygenation. (2020) - Ikegaki, Shunkichi; Otoshi, Takehiro; Hirai, Tomoyuki; Hirabayashi, Masataka
Abstract: Parathyroid crisis, which might occur during the natural history of primary hyperparathyroidism, presents fatal hypercalcemia. Although hyperparathyroidism is known to cause metastatic pulmonary calcification, parathyroid crisis with respiratory failure is rarely reported. Here, we present a case of parathyroid crisis with respiratory failure due to parathyroid adenoma. For the first 2 weeks after admission to our hospital, the patient was treated with hydration, calcium-lowering agents, dialysis and extracorporeal membrane oxygenation, with gradual improvement in her respiratory condition as blood calcium levels decreased. However, she still needed oxygen even after that. Therefore, parathyroidectomy was performed on day 48, and she no longer needed oxygen after the surgery. Chest computed tomography scan also demonstrated improvement in pulmonary calcification, although it did not completely disappear even 4 months after parathyroidectomy. Parathyroid crisis is an endocrine emergency, and its possibility should be considered in patients with respiratory failure with hypercalcemia.